A systematic review of comparisons between protocols or registrations and full reports in primary biomedical research - Li, Guowei; Abbade, Luciana P. F. [UNESP]; Nwosu, Ikunna; Jin, Yanling; Leenus, Alvin; Maaz, Muhammad; Wang, Mei; Bhatt, Meha; Zielinski, Laura; Sanger, Nitika; Bantoto, Bianca; Luo, Candice; et al. (Springer Nature, 2018)
Background: Prospective study protocols and registrations can play a significant role in reducing incomplete or selective reporting of primary biomedical research, because they are pre-specified blueprints which are available for the evaluation of, and comparison with, full reports. However, inconsistencies between protocols or registrations and full reports have been frequently documented. In this systematic review, which forms part of our series on the state of reporting of primary biomedical, we aimed to survey the existing evidence of inconsistencies between protocols or registrations (i.e., what was planned to be done and/or what was actually done) and full reports (i.e., what was reported in the literature); this was based on findings from systematic reviews and surveys in the literature. Methods: Electronic databases, including CINAHL, MEDLINE, Web of Science, and EMBASE, were searched to identify eligible surveys and systematic reviews. Our primary outcome was the level of inconsistency (expressed as a percentage, with higher percentages indicating greater inconsistency) between protocols or registration and full reports. We summarized the findings from the included systematic reviews and surveys qualitatively. Results: There were 37 studies (33 surveys and 4 systematic reviews) included in our analyses. Most studies (n = 36) compared protocols or registrations with full reports in clinical trials, while a single survey focused on primary studies of clinical trials and observational research. High inconsistency levels were found in outcome reporting (ranging from 14% to 100%), subgroup reporting (from 12% to 100%), statistical analyses (from 9% to 47%), and other measure comparisons. Some factors, such as outcomes with significant results, sponsorship, type of outcome and disease speciality were reported to be significantly related to inconsistent reporting. Conclusions: We found that inconsistent reporting between protocols or registrations and full reports of primary biomedical research is frequent, prevalent and suboptimal. We also identified methodological issues such as the need for consensus on measuring inconsistency across sources for trial reports, and more studies evaluating transparency and reproducibility in reporting all aspects of study design and analysis. A joint effort involving authors, journals, sponsors, regulators and research ethics committees is required to solve this problem.
Keywords: Biased reporting; Discrepancy; Incomplete reporting; Inconsistency; Protocol; Registration; Selective reporting